WORKSHOP PEMBUATAN MEDIA BELAJAR POWERPOINT, MENTIMETER DAN YOUTUBE BAGI GURU SMK WIDYA NUSANTARA BEKASI - Seta Samsiana; Rahmadya Trias Handayanto; Setyo Supratno; Andi Hasad; Sri Marini; Rika Sylviana; Taufiqur Rakhman; Aeri Sujatmiko (DEVOSI, 2022)
This training provides several materials related to efforts to develop interactive media so that the learning provided becomes more communicative, increasing the interest and quality of student learning, including Video Learning Presenter View Recoder Ms. Power Point, Use of Mentimeter Interactive Media, Uploading Learning Media on Youtube. The purpose of abdimas activities is to introduce several types of learning media that can be an additional reference of knowledge in SMK Widya Nusantara Bekasi in the implementation of teaching and learning activities that are still carried out online. This is a real step from US to improve the ability of teachers to create interactive learning media independently.